ADHD in University Settings: Predictive Validity of Quantitative EEG Coherence. Issue 4 (July 2021) - Bridges, Rachel M.; Decker, Scott L.
Abstract : Purpose: Research has demonstrated distinct patterns of electroencephalography (EEG) coherence with attention-deficit/hyperactivity disorder (ADHD) in children; however, few studies have examined coherence measures in adults with ADHD. Further, specific research examining EEG coherence within the subgroup of young adults in post-secondary education is absent from the literature. Methods: The current study investigated the utility of quantitative EEG in predicting ADHD behavioral symptoms in 35 college students with a documented ADHD diagnosis and 35 control students. Results: Increased interhemispheric frontal beta-wave coherence was found in individuals with ADHD. Logistic regression of principle components of quantitative EEG coherence metrics predicted ADHD group membership. Conclusions: Suggestions for improving ADHD identification in college populations using quantitative EEG are discussed.